2022
DOI: 10.1073/pnas.2204473119
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism for strengthening E-cadherin adhesion using a monoclonal antibody

Abstract: E-cadherin (Ecad) is an essential cell–cell adhesion protein with tumor suppression properties. The adhesive state of Ecad can be modified by the monoclonal antibody 19A11, which has potential applications in reducing cancer metastasis. Using X-ray crystallography, we determine the structure of 19A11 Fab bound to Ecad and show that the antibody binds to the first extracellular domain of Ecad near its primary adhesive motif: the strand–swap dimer interface. Molecular dynamics simulations and single-molecule ato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…S2a, "1ab" condition). Consistent with our previous finding that Ecad strand-swap dimers bound to only one activating antibody cannot strengthened binding (Xie et al, 2022), in the 66E8 1ab condition, the ΔSASA also reached zero at ~800ps, indicating binding cannot be strengthened by only one 66E8 (Supplementary Fig. S2b).…”
Section: E8 Mediated Stabilization Of Strand-swap Dimer Leads To Stro...supporting
confidence: 91%
See 1 more Smart Citation
“…S2a, "1ab" condition). Consistent with our previous finding that Ecad strand-swap dimers bound to only one activating antibody cannot strengthened binding (Xie et al, 2022), in the 66E8 1ab condition, the ΔSASA also reached zero at ~800ps, indicating binding cannot be strengthened by only one 66E8 (Supplementary Fig. S2b).…”
Section: E8 Mediated Stabilization Of Strand-swap Dimer Leads To Stro...supporting
confidence: 91%
“…We recently showed that 19A11 strengthens Ecad adhesion by forming salt bridges that stabilize the β-strand and its complementary binding pocket (Xie et al, 2022). Similarly, cryo-EM suggests that Ecad bound to 19A11 adopts a twisted conformation which may represent a strengthened strand-swap dimer (Maker et al, 2022).…”
Section: Main Textmentioning
confidence: 94%
“…Next, to validate LAB activity with a well-characterized protein and in a different cell line, we fused LAB to the ubiquitous cell-cell adhesion protein E-cadherin (Ecad) in MDCK cells. Ecad plays key roles in the formation and maintenance of epithelial tissues and acts as a tumor suppressor (Xie et al 2022). We fused CIB1 and spTN onto Ecad-EGFP (ECibN) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to use molecular simulation method to study the interaction mechanism of biomolecules on M-β-PG surface. A large number of studies have shown that it is feasible to study the interaction between materials and biomolecules by means of molecular simulation [11][12][13][14]. For example, Hernandez et al [15] selected two monosaccharides of polysaccharides and performed molecular dynamics simulations to investigate the effect of water on their interaction with hydroxyapatite, revealing that the main functional groups interacting were sulphate, carbonyl and carboxyl functional groups.…”
Section: Introductionmentioning
confidence: 99%